EDUKASI IBU HAMIL DALAM UPAYA MENINGKATKAN DERAJAT KESEHATAN MASYARAKAT DI KELURAHAN PAMPANGAN NAN XX KECAMATAN LUBUK BEGALUNG KOTA PADANG - Joserizal Serudji; Lisma Evareny; Iria Ningsih Busri; Izmi Fadhillah Nasution; Novy Ratnasari Sinulingga; Rani Ashari; Salma Afriliza; Yusmalia Hidayati; Yolanda Syahdia; Yusrawati Yusrawati; Desmawati Desmawati; Aldina Ayunda Insani; Vaulinne Basyir; Hudila Rifa Karmila (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
The target of SDGs in 2030 in the 3rd goal is to reduce the Maternal Mortality Rate to below 70 per 100,000 live births, reduce the Neonatal Mortality Rate (AKN) to 12 per 1000 live births and the Infant Mortality Rateto 25 per 1000 live birth. Goal 5 of the SDGs seeks to achieve gender equality, empowering women, including child women. The purpose of this activity is to create a complete understanding in all sectors regarding maternal health services during pregnancy, childbirth, postpartum with preventive and promotive efforts through community assistance efforts on the health and welfare of pregnant women. The method used is providing education to husbands and the community about assisting pregnant women. This activity was carried out in Pampangan Nan XX Village, RW 05 (RT 01 - RT 04), Lubuk Begalung District. The samples in this activity were all husbands, community leaders (TOMA) and religious leaders (TOGA). Based on data collection and interviews, it was found that the community participation was still low in assisting mothers during pregnancy (56%). Implementation is carried out by developing innovations in providing education and health promotion to the community in an effort to improve Community Based Health Business (UKBM). Education is provided in the form of videos and pre-test questions sent via whatsapp group to husbands and the community containing material about efforts to assist pregnant women. The evaluation was carried out by giving post-test questions, the results obtained that all husbands and the community (100%) already had good knowledge about maternal assistance during pregnancy.